Application of Sawi transform in Cryptography - R. Bhuvaneswari, K. Bhuvaneswari (International Journal of Modern Agriculture, 2021)
Cryptography is the science of secret communication. Encryption is a process used to convert the given original text into a secret text known as cipher text. Decryption is a process of converting the cipher text into the original text. In this paper, we discuss an encryption and decryption algorithm based on Sawi transform. We illustrate the algorithms by an example